Legal Implications of Inheritance Distribution in Multicultural Families under Indonesia’s Islamic Law - Cindra Kartika Mokodompit; Mutia Cherawaty Thalib; Nurul Fazri Elfikri; Rasham Armab Saikhu (Yayasan Cendekia Gagayunan Indonesia, 2026)
Inheritance distribution within multicultural families presents legal challenges due to the interaction between Islamic law, customary law, and civil law in Indonesia's plural legal system. Although the Compilation of Islamic Law (KHI) provides normative guidance for inheritance distribution among Muslims, its implementation frequently encounters socio-cultural dynamics that influence legal outcomes. Previous studies have primarily focused on normative Islamic inheritance law or legal pluralism in general, while limited attention has been given to the legal consequences of inheritance distribution in multicultural families under the KHI framework. This study aims to analyze the legal consequences of inheritance distribution in multicultural families from the perspective of the Compilation of Islamic Law. Employing normative legal research, the study applies statutory, conceptual, and case approaches, with qualitative analysis of legal materials comprising legislation, judicial decisions, and relevant legal doctrines. The findings reveal that inheritance distribution in multicultural families operates within a plural legal framework where Islamic law, civil law, and customary law interact dynamically. In practice, inheritance settlement frequently relies on family deliberation rather than strict adherence to the KHI, resulting in greater flexibility but reduced legal predictability. The study further demonstrates that judicial interpretation, including the application of wasiat wajibah, functions as an adaptive mechanism to reconcile legal certainty with substantive justice. This research contributes by linking normative inheritance provisions with social adaptation practices in multicultural family structures and offers a conceptual framework for balancing legal certainty and substantive justice within Indonesia's plural legal system. The findings enrich the discourse on Islamic inheritance law and provide practical guidance for resolving inheritance disputes in culturally diverse societies.